Rehabilitación cardiaca en pediatría: ¿qué dice la evidencia? (2017)
Introduction: In the past four decades, health organizations have acknowledged cardiac rehabilitation as an essential element in the recovery process of patients with cardiovascular disease. Objective: To analyze the evidence on the implementation of a cardiac rehabilitation program based on exercise in pediatric patients with congenital heart defects. Materials and methods: Available evidence of cardiac rehabilitation programs based on physical exercise in pediatric patients with congenital alterations was analyzed. The MeSH terms “Rehabilitation”, “Exercise”, “Resistance Training” and “Pediatrics” were used for the search in the Ebsco, Pedro, Hinari, Elsevier, Science Direct, Springer and Medline databases. Results: The implementation of a cardiac rehabilitation program in the pediatric population has a significant impact on the quality of life of these patients, although establishing parameters such as evaluation, rehabilitation protocol, physical exercise prescription and assessment of quality of life is still necessary. Conclusions: Creating a standardized and ratified cardiac rehabilitation protocol for the pediatric population with congenital heart disease based on physical exercise is necessary. © 2017, Universidad Nacional de Colombia. All rights reserved.